AS AN IMPORTANT ELEMENT OF THE CRIMINALISTIC DESCRIPTION OF CASES OF CRIMES COMMITTED IN THE FIELD OF CONSTRUCTION - Khursandovich, Karaev Alisher (PT ANTIS International Publisher, 2024)
This article is devoted to one of the most relevant issues of today, that is, economic crimes committed in the construction sector, in which the circumstances of economic crimes in the construction sector, the circumstances that must be proven in the investigation, the methods of the crime, the criminalistic circumstances of the crime, in the development of investigative versions, ways to effectively plan and conduct investigative actions, use tactical methods, engage in psychological communication with the suspect, the accused.